Pickering emulsions: challenges and opportunities in topical delivery. (2nd August 2016) - Marto, Joana; Ascenso, Andreia; Simoes, Sandra; Almeida, António J.; Ribeiro, Helena M.
ABSTRACT: Introduction : Topical drug delivery is a challenging area with many advantages such as avoidance of first passage effect, stabilization of blood concentrations and attainment of local therapeutic effect with fewer side effects. Despite all these advantages, topical drug delivery remains limited to few molecules, since skin acts as a barrier to the delivery of many therapeutic molecules. To overcome this obstacle, a favored strategy relies on selecting suitable vehicles for dermatologic therapy, such as emulsions, gels and, more recently, nanoparticulate systems. Areas covered : Particle-stabilized emulsions, also known as Pickering emulsions, have garnered interest in recent years. Although most of the investigation on Pickering emulsions has been based on model systems with inorganic or organic solid particles, recent advances have been made regarding the application of nanocarriers, protein-based particles or cyclodextrins for this purpose. This review reports the latest advances in Pickering emulsions technical challenges, and discusses the potential benefits and drawbacks of using these formulations for topical pharmaceutical and cosmetic applications as an alternative to conventional surfactant-based systems. Expert opinion : Pickering emulsions appear as a multifunctional dosage form with endless advantages. A great deal of progress is expected in this area, which might represent a renewed vision for the pharmaceutical and cosmetic industry.